Temperature‐Sensitive Structural Speciation of Cobalt‐Iminodialcohol‐(N, N'‐Aromatic Chelator) Systems: Lattice Architecture and Spectrochemical Properties. Issue 30 (21st July 2020) - Matsia, Sevasti; Menelaou, Melita; Hatzidimitriou, Antonios; Tangoulis, Vassilis; Lalioti, Nikolia; Ioannidis, Nikolaos; Blömer, Laura; Kersting, Berthold; Salifoglou, Athanasios
Abstract : Temperature‐sensitive crystalline phases, pertaining to discrete clusters of binary and ternary Co(II, III):iminodipropanol:(N, N'‐aromatic binder) systems, were prepared. The rich structural speciation of such systems in alcoholic media and their unique structural, magnetic, and spectroscopic profiles have been demonstrated. The need to understand the chemical reactivity of such complex ternary Co(II)‐(1, 1'‐iminodi‐2‐propanol) systems, in the presence of N, N'‐aromatic chelators 2, 2'‐bipyridine and 1, 10‐phenanthroline and aromatic binder 4, 4'‐bipyridine in methanol, led to the synthetic development of well‐defined hybrid metal‐organic materials with discrete spectroscopic, structural, electrochemical, and magnetic properties. The surprisingly plethoric family of the prepared mononuclear‐trinuclear‐tetranuclear Co(II, III) clusters was characterized through elemental analysis, FT‐IR, and X‐ray crystallography. Enrichment of their physicochemical profile originated from electrochemical, optical (UV/Vis, luminescence), magnetic, and EPR studies, unequivocally supporting their structural formulation. Collectively, the experimentally and theoretically (Bond‐Valence‐Sum, Hirshfeld) perused structures project the influence of molecular stoichiometry and temperature on targeted synthetic efforts toward crystal engineering of discrete Co(II, III)‐center assemblies, exemplifying structure‐reactivity correlations and magneto‐optical‐structural attributes. Abstract : Structural speciation of Co(II):iminodipropanol:N, N'‐aromatic chelator systems, under temperature‐specific conditions, reveals binary‐ternary hybrid metal‐organic coordination compounds of mono‐, tri‐, and tetranuclear Co(II, III) centers. Octahedral Co(II, III) cluster arrangements project distinct optical and magnetic properties, thereby establishing lattice architecture‐magneto‐optical correlations useful in the development of advanced materials.